Telework: a comparative analysis of the Portuguese and Spanish legal-labour regime - OURO, Marisa (Revista Jurídica Portucalense, 2022)
The main objective is to analyse and compare the current Portuguese legislation on the telework regime, contained in Law 83/2021 of 6 December, and the current Spanish legislation, contained in Law 10/2021, of 9 July. These legislations resulted from the COVID-19 pandemic, the subsequent economic crisis, and the need to use telework to contain contamination. Both legal systems benefit from the same EU Law, and both got inspiration from the 2002 European Framework Agreement on Telework. However, Portuguese and Spanish laws chose different strategies in approaching the telework regime, which had repercussions on their legal drafting. Thus, in the Spanish case, collective bargaining was prioritised, while in the Portuguese case, the legislator himself delimited the worker's rights as much as possible. Each of these approaches has positive aspects, but they also present points that could be improved and which we will analyse.